Pembelajaran Seni Tari dalam Membentuk Karakter dan Kreativitas Peserta Didik di Sekolah Dasar - Dwi Andini; Jauhari Kumara Dewi; Khai Runnisa (IBTIDAIYAH: Jurnal Penelitian dan Pendidikan Dasar Islam, 2025)
Dance learning is an important part of elementary education because it plays a role in developing the physical, mental, social, emotional, and creative aspects of students. Dance is not only understood as a movement activity, but also as a medium of artistic expression, a means of nonverbal communication, and a vehicle for instilling values and preserving culture. This study aims to examine and describe the role of dance learning in developing elementary school students' learning creativity holistically. This study uses a qualitative approach with a literature study method through an analysis of 51 national journal articles relevant to dance learning and creativity development. Data were obtained from various scientific sources, then analyzed through the stages of collection, reduction, presentation, and drawing conclusions. The results of the study indicate that dance learning can enhance students' creativity through exploration, improvisation, and movement composition activities, as well as fostering self-confidence, communication skills, and cooperation. In addition, dance contributes to shaping students' personalities and supports the preservation of cultural arts from an early age. Dance learning has been proven to have a positive impact in creating a creative and meaningful learning environment